Building Sustainable Competitive Advantage Through Customer Centricity: Evidence from FMCG Firms in Indonesia - Damanik, Oskar Fajar; Simangunsong, Elliot; Rahman, Fathony; Ardianto, Eka (UI Scholars Hub, 2026)
Research Aims: This study aims to develop a comprehensive model that leverages customer-centric strategies to build sustainable competitive advantage within the dynamic and complex context of changing consumer behaviour. Design/Methodology/Approach: Data were obtained from 235 sales and marketing managers across 63 Fast Moving Consumer Goods (FMCG) firms using a convenience sampling method. A structured questionnaire employing Likert-scale items was distributed via Google Forms. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS 3 and further validated through semi-structured interviews with top management practitioners. Research Findings: The findings of the study indicate that a customer-centric strategy has a significant direct influence on sustainable competitive advantage, and is primarily influenced by internal factors of organisational culture and knowledge management. External factor of local market conditions were not significant determinants. Theoretical Contribution/Originality: This research fills a critical gap in the academic literature by offering a customer-centric strategy model specifically adapted for firms operating in emerging markets like Indonesia. Managerial Implication in the Southeast Asian Context: The insights provided are valuable for practitioners in the highly competitive FMCG landscape of Indonesia, equipping them with strategic guidance to better align with changing consumer behaviour in the market. Research Limitation & Implications: This study is situated within Indonesia's FMCG sector and thus its generalizability across other industries or organisational context may be limited.